Exploitation of the Escherichia coli lac operon promoter for controlled recombinant protein production. (10th April 2019) - Browning, Douglas F.; Godfrey, Rita E.; Richards, Kirsty L.; Robinson, Colin; Busby, Stephen J.W.
Abstract : The Escherichia coli lac operon promoter is widely used as a tool to control recombinant protein production in bacteria. Here, we give a brief review of how it functions, how it is regulated, and how, based on this knowledge, a suite of lac promoter derivatives has been developed to give a controlled expression that is suitable for diverse biotechnology applications.